Hydrodynamic characterisation of macromolecules in cucurbits - Jiwani, Shahwar (2016)
This thesis comprises of the study performed on the extraction, isolation and structural characterisation of macromolecular components from the three members of the family Cucurbitaceae. In particular, the polysaccharides from C.moschata, C. maxima and C. pepo (butternut squash, zucchini and pumpkin, respectively) and oil bodies from the seeds of C. pepo are selected on the basis of their antidiabetic potential.